HUBUNGAN PENGETAHUAN DAN SIKAP PADA AKSEPTOR KB TENTANG KONTRASEPSI DALAM PEMILIHAN METODE KONTRASEPSI HORMONAL DI PUSKESMAS RAWAT INAP SIDOMULYO KOTA PEKANBARU - Lasiah Susanti; Nabilla Rahma Putri; Neni Ristiani (LPPM Universitas Abdurrab, 2025)
The hormonal contraceptives such as pills, injectable, and implants were still the most chosen contraceptive methods in Indonesia, including in Sidomulyo Inpatient Public Health Center (Puskesmas Rawat Inap Sidomulyo) of Pekanbaru. The choice of contraceptive methods is affected by users knowledge and attitudes, however, continuity of use is often hindered by incompatibility with medical conditions and users perceiveness.This study aimed to analyze the association between level of knowledge and attitudes with choosing hormonal contraceptive methods and to assess their suitability with the Medical Eligibility Criteria (MEC). This study using quantitative analytic design with a cross-sectional approach on 57 subjects. Data were collected using structured questionnaires and analyzed univariately and bivariately. The results showed that most subjects had sufficient knowledge and a positive attitude toward hormonal contraceptives, but the bivariate analysis using Chi square test revealed no significant relationship between knowledge and the choice of hormonal contraceptive methods (p = 1.000) nor between attitude and the choice of hormonal contraceptive methods (p = 0.670). Although according to MEC most contraceptive choices were compatible to user medical condition, few users still choosing methods that were incompatible for them. This study recommends strengthening prompt comprehensive education, not only to ensure informed choices of contraceptive methods, but also help users to choose the compatible method for their medical condition. Thus, increasing contraceptive continuity.